2017
DOI: 10.4236/ojog.2017.75061
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual Abnormalities and Gynaecological Problems in Women on Anticoagulant and Antiplatelet Therapy: Management Options

Abstract: Introduction: The aim of this study was: 1) To study the pattern of menstrual abnormality and severity in women on anticoagulant and antiplatelet drugs. 2) To analyze the correlation of prothrombin time (PT), International Normalised ratio (INR) and the bleeding severity. 3) To discuss the various management options in unexpected emergencies and menstrual complications in this subset of women on anticoagulants. Material & Methods: It is a prospective study, over a period of 18 months from July 2011 to december… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…In addition, we demonstrated a comparable prevalence of HMB in women receiving antiplatelet and anticoagulant therapy. This finding aligns with a previous study that reported a high frequency of menstrual problems in those receiving antiplatelets and anticoagulants 11 . However, this number was almost twofold higher than in the general population which is estimated at 9% to 18% 23‐25 .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In addition, we demonstrated a comparable prevalence of HMB in women receiving antiplatelet and anticoagulant therapy. This finding aligns with a previous study that reported a high frequency of menstrual problems in those receiving antiplatelets and anticoagulants 11 . However, this number was almost twofold higher than in the general population which is estimated at 9% to 18% 23‐25 .…”
Section: Discussionsupporting
confidence: 91%
“…This finding aligns with a previous study that reported a high frequency of menstrual problems in those receiving antiplatelets and anticoagulants. 11 However, this number was almost twofold higher than in the general population which is estimated at 9% to 18%. 23 , 24 , 25 This indicates that physicians should be aware of HMB as a prevalent and morbid bleeding complication in women receiving anticoagulant and antiplatelet therapy.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…A study of 90 women, aged 15–49 years, reported that the abnormal uterine bleeding was reported by 17.8% women before use of anticoagulation therapy while 29.5% women reported this problem after the start of anticoagulants 12. The treatment of HMB is quite challenging and the efficacy of commonly used medicines like Tranexamic acid is not well established 13. The other pharmacological options include Levonorgestrel intrauterine system, high dose progestin-only therapy, and combined hormonal contraceptives.…”
Section: Discussionmentioning
confidence: 99%